STEPAR: an automatic code to infer stellar atmospheric parameters - Tabernero, H. M.; Marfil, E.; Montes, D.; González Hernández, J. I. (Astronomy and astrophysics (Berlin), 2019)
Context. STEPAR is an automatic code written in Python 3.X designed to compute the stellar atmospheric parameters Teff, log g, [Fe/H], and ξ of FGK-type stars by means of the equivalent width (EW) method. This code has already been extensively tested in different spectroscopic studies of FGK-type stars with several spectrographs and against thousands of Gaia-ESO Survey UVES U580 spectra of late-type, low-mass stars as one of its 13 pipelines. Aims. We describe the code that we tested against a library of well characterised Gaia benchmark stars. We also release the code to the community and provide the link for download. Methods. We carried out the required EW determination of Fe I and Fe II spectral lines using the automatic tool TAME. STEPAR implements a grid of MARCS model atmospheres and the MOOG radiative transfer code to compute stellar atmospheric parameters by means of a Downhill Simplex minimisation algorithm. Results. We show the results of the benchmark star test and also discuss the limitations of the EW method, and hence the code. In addition, we find a small internal scatter for the benchmark stars of 9 ± 32 K in Teff, 0.00 ± 0.07 dex in log g, and 0.00 ± 0.03 dex in [Fe/H]. Finally, we advise against using STEPAR on double-lined spectroscopic binaries or spectra with R <  30 000, S/N <  20, or v sin i >  15 km s−1, and on stars later than K4 or earlier than F6.